Distal extracellular teneurin region (teneurin C-terminal associated peptide; TCAP) possesses independent intracellular calcium regulating actions, in vitro: A potential antagonist of corticotropin-releasing factor (CRF) - David W. Hogg; Claudio C. Casatti; Denise D. Belsham; Dalia Baršytė-Lovejoy; David A. Lovejoy (Biochemistry and Biophysics Reports, 2022)
Teneurin C-terminal associated peptides (TCAP) are natural bioactive peptides that possess anxiety-reducing roles in animals, in vivo, and increase cell viability, in vitro. Although these peptides have some primary structural similarity to corticotropin-releasing factor (CRF), they are derived from the distal extracellular region of the teneurin transmembrane protein where they may act as separate soluble peptides after auto-catalytic cleavage from the teneurin protein following interaction with the cognate teneurin receptor, latrophilin (ADGRL), or expressed as a separate mRNA. However, although the signal transduction mechanism of TCAP in neurons has not been established, previous studies indicate an association with the intracellular calcium flux. Therefore, in this study, we have characterized the TCAP-mediated calcium response in hypothalamic cell lines using single-cell calcium methods with pharmacological antagonists to identify potential calcium channels, in vitro. Under normal circumstances, TCAP-1 reduces cytosolic calcium concentrations by uptake into the mitochondria and efflux through the plasma membrane independently of the teneurins. In doing so, TCAP-1 could inhibit the potential ‘stress’ -inducing actions of CRF.